Relação de variáveis com o desempenho de estudantes na educação profissional a distância - Dalcin, Eduardo (2021)
This thesis aims to analyze the relationship of some variables with the performance of EaD/IFFAR students in Professional Education. As research methodology, was used to search action within the school environment, with the aid of statistical methods for analyzing the results. Based on the analysis of the EaD/IFFAR (2015) student profile survey, carried out in the initial studies in 2018, the main variables that will be part of the study are mapped. In the 1st Cycle (Diagnostic Action Survey 2018/2019), through the collection of data carried out by questionnaire and administrative reports of Moodle, graphs, data table and descriptive measures of the variables are elaborated that will serve as base for the next cycles of the research. In the 2nd Cycle (Discipline Intervention 2020), the researcher teacher, together with the full professor of the discipline, participates in the pedagogical actions in the discipline Environment in EaD in Moodle, participating in actions related to the structuring of the discipline, preparation of teaching material, study activities and evaluation. Thus, relevant observations and reflections are made regarding the process of interaction, interactivity, problematization and collaboration of students. At the 3rd cycle (Definition Structural Model 2020/2021), through a new data collection carried out through questionnaires and administrative reports of Moodle, carried out the preparation of charts and tables of data. The variables to be analyzed are mapped through the use of Exploratory Factor Analysis (EFA), where several actions related to the variables are carried out: Student Assignments, Teacher Assignments, Infrastructure, Student Quality of Life and Performance. As the final purpose of this thesis research, a Structural Model is elaborated that illustrates the relationships of these study variables with the performance of the EaD/IFFAR Student, using the computational application PLS-SEM. The research was based on the theoretical assumptions of Vigostky, through the social-interactionist theory and Paulo Freire through the dialogical-problematic conception, in addition to public policies for Professional and Technological Education (EPT). Thus, it is concluded that the confirmation of the research hypothesis which relates the Student's Attributions with their Performance in EaD/IFFAR, in addition to having a direct and positive relationship, registered the highest explanation coefficient indexes, also containing the highest index in the model, being ranked with the highest search effect and significantly.